Analytical Science - Chapter 13 - Woodget, Brian (The University of Hull)
This chapter considers the important technique of mass spectroscopy from the viewpoint of the analytical scientist rather than that of the interpretative spectroscopist. Topics covered include fundamentals of MS, ionisation modes, brief descriptions of instrumentation and the use of MS as a detector in other analytical technologies –hyphenated techniques.